1986
DOI: 10.1210/endo-119-4-1786
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Insulin Receptors and Modulation of Alkaline Phosphatase Activity by Insulin in Rat Osteoblastic Cells*

Abstract: Osteoporosis is a known complication of diabetes mellitus, suggesting a role for insulin in bone homeostasis. We studied insulin receptors and insulin action in the osteoblast-like rat osteogenic sarcoma cell line ROS 17/2.8. These cells share many common features with the osteoblast, such as 1,25-dihydroxyvitamin D3 receptors, PTH receptors, and 1,25-dihydroxyvitamin D3-induced modulation of alkaline phosphatase activity and osteocalcin. Competition binding studies revealed high affinity insulin receptors, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 30 publications
0
52
0
1
Order By: Relevance
“…Thus, maximal insulin binding by hepatocytes coincides with the insulin concentration range present in the insulin concentration wavefront within a pulse presented to the liver in the portal vein, ϳ1,000 -4,000 pmol/l. In contrast, hepatocyte insulin binding is much less avid at insulin concentrations typically present in the trough of an insulin pulse train, which represents a basal nonpulsatile component of release (32)(33)(34). High binding in insulin pulses would be expected to result in endocytosis of a high proportion of insulin delivered to the hepatic sinusoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, maximal insulin binding by hepatocytes coincides with the insulin concentration range present in the insulin concentration wavefront within a pulse presented to the liver in the portal vein, ϳ1,000 -4,000 pmol/l. In contrast, hepatocyte insulin binding is much less avid at insulin concentrations typically present in the trough of an insulin pulse train, which represents a basal nonpulsatile component of release (32)(33)(34). High binding in insulin pulses would be expected to result in endocytosis of a high proportion of insulin delivered to the hepatic sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from all study participants. Five healthy subjects (two men and three women) mean age 32 years (range [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], with a mean BMI of 24.9 kg/m 2 (21.2-27.1) participated. All subjects were nondiabetic based on fasting plasma glucose concentration (mean fasting plasma glucose 5.4 mmol/l [5.1-5.8]) and HbA 1c values (mean 4.8% [4.5-5.0]).…”
Section: Methodsmentioning
confidence: 99%
“…The Ca release from bone tissue does not seem to be concerned to its mechanism, because plasma PTH levels were significantly suppressed during the clamp. However, the presence of insulin receptor in osteoblastic cells (Levy et al 1986) and lower plasma Ca levels in diabetic rats (Ishida et al 1988) suggest the insulin action on bone tissue. Thus, the direct effects of insulin on bone tissue may contribute to the increased plasma ionized Ca levels caused by hyperinsulinemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, circumstantial evidence suggesting this possibility has been recently published: Levy et al [19] reported a decrease in the total activity of alkaline phosphatase in rat osteoblastic cells after chronic (24 h) insulin treatment. Similarly, the content of heparan sulfate proteoglycan, another anchored protein, was lowered by exposure of cells to insulin for 12 h [20].…”
Section: Discussionmentioning
confidence: 99%